Autonomous bidding agents : strategies and lessons from the trading agent competition - Wellman, Michael P. (Intelligent robotics and autonomous agents., 2007)
Overview and analysis of algorithmic advances developed within an integrated bidding agent architecture that emerged from recent research in a growing domain of AI.